Lane Type Classification & Distance Measurement System for Autonomous Vehicle - Ozen, Sinan; Kaya, Uygar; Semiz, Abdurrahim; Yalcin, Mustafa Fatih; Celebi, Aysun Tasyapi (IEEE, 2023)
In this paper, lane type classification and lane distance measurement system are proposed for autonomous vehicles. In the proposed system, the perspective transformation method is applied to the image taken from the vehicle camera, so that a bird's-eye view is obtained and the parts with stripes are cropped from the image, and then a multi-class classification model is implemented using neural network-based architectures to determine the stripe type. In addition, with the proposed distance measurement system, the distance of the vehicle to the right and left lanes is calculated during autonomous driving, thus ensuring that the vehicle can drive autonomously on the lane. For this study, our own data set has been created.
Keywords: deep learning; image processing; custom dataset; lane type classification; lane distance measurement; Computer Science; Communication; Engineering; Telecommunications